Ex Aequo Et Bono and the Quest for Arbiter Independence in Deciding a Case - Herdi Hadylaya, Michael (LPPM Universitas Ekasakti Padang, 2024)
Arbitration is a dynamic practice that can be developed from many perspectives. One of the issues to consider is the implementation of ex aequo et bono by arbitrators, which many parties see as requiring prior approval from the parties so that arbitrators can make decisions based on ex aequo et bono. This study concludes that the arbitrator's authority to decide ex aequo et bono is not derived from the parties' agreement but rather from the arbitrator's inherent authority. First, because this principle is consistent with the spirit of arbitration, the Arbitrator has the authority to decide ex aequo et bono. Second, the Law on Judicial Power imposes an obligation to investigate, adhere to, and comprehend legal values and the sense of justice in society. Third, no provision in the Arbitration Law requires the parties to agree in advance on the grant of ex aequo et bono. As a result, the current arbitration practice does not violate the Arbitration Law as long as some parties request an ex aequo et bono award in their petitum.